1997
DOI: 10.1200/jco.1997.15.3.1071
|View full text |Cite
|
Sign up to set email alerts
|

Phase I and pharmacologic study of docetaxel and cisplatin in patients with advanced solid tumors.

Abstract: The dose levels docetaxel 100 mg/m2 plus cisplatin 75 mg/m2 and docetaxel 85 mg/m2 plus cisplatin 100 mg/m2 appeared to be manageable. At these dose levels, the median relative dose-intensity was high and 81% and 88% of all cycles, respectively, could be given at full dose. Schedule A is advocated for further treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
3

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 18 publications
1
25
0
3
Order By: Relevance
“…The present study evaluated docetaxel in combination with cisplatin which is generally considered to be the most active agent against urothelial cancer. Prior phase I studies showed the feasibility of this combination and its activity on different tumours (Pronk et al, 1997). The response rate observed for urothelial cancer in our study is within the range of the responses seen with other conventional (Sternberg et al, 1989) and newer schedules (Von der Maase et al, 1999;Dreicer et al, 2000) which are considered highly active.…”
Section: Discussionsupporting
confidence: 78%
“…The present study evaluated docetaxel in combination with cisplatin which is generally considered to be the most active agent against urothelial cancer. Prior phase I studies showed the feasibility of this combination and its activity on different tumours (Pronk et al, 1997). The response rate observed for urothelial cancer in our study is within the range of the responses seen with other conventional (Sternberg et al, 1989) and newer schedules (Von der Maase et al, 1999;Dreicer et al, 2000) which are considered highly active.…”
Section: Discussionsupporting
confidence: 78%
“…The incidence of sensory neuropathy of the combination was slightly higher than the incidence reported for docetaxel as a single agent (49%) (Hilkens et al, 1996). In a phase I study combining paclitaxel and cisplatin and in a phase I study on the docetaxel-cisplatin combination (Hilkens et al, 1997;Pronk et al, 1997), the incidence of sensory neuropathy of the combination was higher than that reported for docetaxel as a single agent (Hilkens et al, 1996). It was suggested that these agents act synergistically in producing neurotoxicity.…”
Section: Discussionmentioning
confidence: 86%
“…Subsequent studies, however, consistently raised concerns about toxicity, notably neutropenia. 1,20,21 Preclinical studies have demonstrated that docetaxel modulates the intracellular metabolism of other drugs (5-FU and cisplatin), which explains the mechanism underlying the synergistic effect.…”
Section: Discussionmentioning
confidence: 99%